Analisis Manajemen Pembinaan Prestasi dan Aspek Psikologi pada Atlet SSB Diktra Prima dan SSB Aruman Jaya Kotamobagu - molanu, ibnu taufiq; Setyawati, Heny; Soenyoto, Tommy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to analyze POAC management at SSB Diktra Prima and SSB Aruman Jaya and the psychological aspects of athletes. They are judging from human resources, funding, infrastructure, and training programs. The method used in this research uses a qualitative approach with a SWOT analyst research design. The research results show that in the Management Analysis of Achievement Development and Psychological Aspects of SSB Diktra Prima and SSB Aruman Jaya Kotamobagu Athletes. Human resource planning at both SSBs is vital. Human resource planning is carried out because of the great concern of the sub-district government, youth, and the community, which are highly dedicated to the progress of football schools. The weaknesses in organizing (weaknesses) are that both SSBs have resources that still need to be more effective, funding is still tricky, and facilities and infrastructure still need to be improved. The implementation (actuating) of the second SSB training program follows the existing football curriculum in Indonesia. Athletes with advantages in playing will have the opportunity to participate in Porprov or PON through selection. Supervision (controlling) is carried out during training and matches. The psychological aspect of the two SSBs is one of the important things that administrators pay attention to, such as the emotional aspects, anxiety, motivation, and self-confidence felt by athletes, both from the causes and how to overcome them. In conclusion, the two SSBs almost have the same POAC and Psychological Aspects analyzed from SWOT, but the most visible difference is in funding.. Keyword analysis, Achievement Development Management, Football Schools, Psychological Aspects of Athletes,